Periodic packets in energy-aware wireless networks - Alghamdi, M. (2008 5th IEEE International Conference on Mobile Ad Hoc and Sensor Systems, 2008)
Existing packets scheduling algorithms designed for energy-efficient wireless networks ignore important features of periodic packets, thereby being inadequate for periodic packets with energy constraints. To remedy this problem, I present in this paper an approach to scheduling periodic packets in wireless networks subject to both timing and energy constraints. I propose a necessary and sufficient feasibility check for a set of periodic packets to be transmitted over a wireless link. Next, I develop an algorithm to schedule periodic packets (or ESPP for short) over a wireless link. The ESPP algorithm aims at minimizing energy dissipation of periodic packets without missing deadlines of periodic packets. I show through simulation studies that ESPP can significantly reduce energy consumption of wireless networks by an average of 46.4% while guaranteeing timing constraints of periodic packets.